Aesthetics of the everyday: Rancière's theory of the emancipated spectator and its relevance to contemporary art practices - Yılmaz, Elif (İstanbul Bilgi Üniversitesi, 2024)
Bu tez, yirminci yüzyıl avangard hareketleriyle birlikte ortaya çıkan izleyicilerin aktif katılımıyla sanat ve toplumun özgürleşme kavramını incelemektedir. Ayrıca, bu tezin amacı, gündelik yaşamın çağdaş sanat pratiklerine yansımalarını Rancière'in özgürleşen seyirci kuramı bağlamında incelemektir. Bu tezde, Dada, Sitüasyonist Enternasyonel, Fluxus, Happening ve Minimalizm gibi avangard akımlar, çağdaş sanat ile gündelik hayat arasındaki ilişkiyi ve aynı zamanda Rancière'in özgürleşen seyirci kuramını anlamak açısından tarihsel referanslar ve rehberlik sağladığı için incelenmiştir. Bu çerçevede, izleyici ve sanatçının özgürleşme potansiyeli, özellikle Rancière'in özgürleşen seyirci teorisi ile ele alınmıştır. Çağdaş sanat eserleri, gündelik hayat ve Rancière'in özgürleşen seyirci teorisi bağlamında analiz edilmiştir. Bunun yanında, gündelik hayatın estetiği, aşinalık, yabancılık ve mekan kavramları üzerine odaklanarak incelenmiştir. Tezde, gündelik hayatın estetiği, gündelik nesnelerin işlevsel sınırlarının dışında sahip oldukları varoluş ve gündelik hayatın sosyal ve katılımcı estetiği üzerinden ele alınmıştır. Gündelik hayatın estetiği incelenirken, gündelik hayat nesnelerini içeren ve izleyici katılımını vurgulayan çağdaş sanat eserleri örnek olarak verilmiştir ve bu eserler, Rancière'in estetik felsefesi ve özgürleşen seyirci kuramı bağlamında incelenmiştir.

This thesis examines the concept of the liberation of art and society through the active participation of viewers, which emerged alongside twentieth-century avant-garde movements. Additionally, the purpose of this thesis is to examine the reflections of everyday life in contemporary art practices within the context of Rancière's theory of the emancipated spectator. In this thesis, avant-garde approaches are primarily examined through movements such as Dada, the Situationist International, Fluxus Happenings, and Minimalism, as they provide historical references and guidance for understanding the relationship between contemporary art and everyday life, as well as the concept of the emancipated spectator. Within this framework, the potential for emancipation of both the audience and the artists is examined, with a particular focus on its discourse within Rancière's theory of the emancipated spectator. Contemporary artworks are analyzed through the lens of the avant-garde approaches and Rancière's theory of the emancipated spectator. Additionally, the aesthetics of everyday life have been examined by addressing the concepts of familiarity, strangeness, and place. In this thesis, the theory of everyday life has been investigated through the lens of existence that goes beyond the functions of everyday objects, as well as through the social and participatory aesthetics of everyday life. While examining the aesthetics of the everyday, selected contemporary artworks that incorporate objects from everyday life and emphasize viewer participation are exemplified. These works are analyzed considering Rancière's philosophy of aesthetics and his theory of the emancipated spectator.
Gündelik hayatın estetiği: Rancière'in özgürleşen seyirci kuramının çağdaş sanat pratikleriyle ilişkisi
Lisansüstü Programlar Enstitüsü, Kültürel İncelemeler Ana Bilim Dalı
Keywords: Felsefe; Philosophy; Güzel Sanatlar